2000
DOI: 10.1088/1126-6708/2000/07/055
|View full text |Cite
|
Sign up to set email alerts
|

Field correlators in Abelian-projected theories and stochastic vacuum model

Abstract: The bilocal electric field strength correlators in Abelian-projected SU(2)-and SU(3)-theories are derived with accounting for the contributions to these quantities brought about by the virtual vortex loops, built out of the dual Nielsen-Olesen strings. Owing to the screening of magnetic charge of the dual vector bosons in the gas of such loops, these bosons become heavier, which leads to the respective change of the correlation length of the vacuum in the models under study. Besides that, it turns out that suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
0
26
1
Order By: Relevance
“…To model the grand canonical ensemble of closed strings, one can proceed along the lines of ref. [27]. Namely, one can use the fact that these strings are short-living (virtual) objects, whose typical sizes are much smaller than the typical distances between them; therefore, similarly to monopoles in the 3-d Georgi-Glashow model, closed strings form a dilute plasma.…”
Section: Corrections Due To the Higgs Field And Closed Stringsmentioning
confidence: 99%
“…To model the grand canonical ensemble of closed strings, one can proceed along the lines of ref. [27]. Namely, one can use the fact that these strings are short-living (virtual) objects, whose typical sizes are much smaller than the typical distances between them; therefore, similarly to monopoles in the 3-d Georgi-Glashow model, closed strings form a dilute plasma.…”
Section: Corrections Due To the Higgs Field And Closed Stringsmentioning
confidence: 99%
“…Ref. [68] for a similar situation in the plasma of closed dual strings in the Abelian-Higgs-type models]. The only thing which matters is the normalization 1 zn(τ ) = 1, that will be implied henceforth.…”
Section: Generalization To the Su(n )-Analogue Of 4d Compact Qed Withmentioning
confidence: 98%
“…Such calculations have been initially performed in various Abelian models, where confinement is provided by the monopole condensation. Those include the 3D Georgi-Glashow model and the 4D compact QED [116,117], as well as the 4D dual Abelian Higgs model in the London limit and its [U (1)] N−1 -symmetric generalization [118][119][120][121][122]. In this way, it has been explicitly shown that the vacuum correlation lengths in all these models are equal to the inverse masses of the corresponding dual vector bosons.…”
Section: Correlation Lengths Of the Stochastic Yang-mills Fieldsmentioning
confidence: 99%